2020
DOI: 10.5535/arm.20055
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Extracorporeal Shockwave Therapy on Cervical Myofascial Pain Following Neck Dissection Surgery: A Randomized Controlled Trial

Abstract: Objective To investigate the efficacy of extracorporeal shockwave therapy (ESWT) on cervical myofascial pain following neck dissection in reducing pain and improving cervical range of motion (ROM).Methods Forty-six patients with cervical myofascial pain following neck dissection surgery were recruited and subdivided at random into two equal groups. The ESWT group received ESWT once a week for 4 weeks (0.25 mL/mm<sup>2</sup>, 1,000 shocks) and a topical non-steroidal anti-inflammatory drug (3 times/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
0
15
0
4
Order By: Relevance
“…However, this method has a poor energy transfer effect and a low pain relief rate. The control group in previous studies (12,14,15,18) was treated with ultrasound-guided pulsed radiofrequency, but the rate of pain relief was worse than that of ESWT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this method has a poor energy transfer effect and a low pain relief rate. The control group in previous studies (12,14,15,18) was treated with ultrasound-guided pulsed radiofrequency, but the rate of pain relief was worse than that of ESWT.…”
Section: Discussionmentioning
confidence: 99%
“…All studies (10,(12)(13)(14)(15)(16)(17)(18)(19) reported the comparison of pain after treatment between the experimental group and the control group using ESWT. There was statistical heterogeneity between the studies (I 2 =85%, P<0.00001).…”
Section: Pain After Treatment (Vas)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rahbar et al [39] compared the efficacy of ESWT to conventional treatments such as ultrasound, hot packs, and self-stretches, and they found that ESWT was superior in reducing discomfort. Kamel et al [40] investigated the impact of ESWT versus regional non-steroidal antiinflammatory medication following neck dissection on pain threshold and intensity for 4 weeks and concluded that ESWT had more significant effects on pain intensity and threshold. The findings of the present trial indicated an increase in SSR latency, which may be due to the anatomical correlation among afferent pain fibers and sympathetic fibers, given that they are parallel within the central nervous system [41].…”
Section: Discussionmentioning
confidence: 99%
“…Rahbar et al [ 39 ] compared the efficacy of ESWT to conventional treatments such as ultrasound, hot packs, and self-stretches, and they found that ESWT was superior in reducing discomfort. Kamel et al [ 40 ] investigated the impact of ESWT versus regional non-steroidal antii-nflammatory medication following neck dissection on pain threshold and intensity for 4 weeks and concluded that ESWT had more significant effects on pain intensity and threshold.…”
Section: Discussionmentioning
confidence: 99%